2022
DOI: 10.3390/ijerph191811271
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Access to Care during the COVID-19 Pandemic: Results from the LOckdown and LifeSTyles (LOST) in Lombardia Project

Abstract: The COVID-19 pandemic disproportionally affected older people in terms of clinical outcomes and care provision. We aimed to investigate older adults’ changes in access to care during the pandemic and their determinants. We used data from a cross-sectional study (LOST in Lombardia) conducted in autumn 2020 on a representative sample of 4400 older adults from the most populated region in Italy. Lifestyles, mental health, and access to healthcare services before and during the pandemic were collected. To identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…extensive evidence has been produced on the changes in access to care during the cOVID-19 emergency in terms of generalised reductions in the use of healthcare services [19,29]. however, to the best of our knowledge, very few studies have investigated the impact of the pandemic on changes in the use of home services among community-dwelling older adults [10,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…extensive evidence has been produced on the changes in access to care during the cOVID-19 emergency in terms of generalised reductions in the use of healthcare services [19,29]. however, to the best of our knowledge, very few studies have investigated the impact of the pandemic on changes in the use of home services among community-dwelling older adults [10,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the cOVID-19 pandemic greatly impacted frailer older adults (i.e. with co-morbidities and mental health disorders [17][18][19]) who more frequently experienced increased use of health and social services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that they are the same disadvantaged groups such as those with low socioeconomic status, health problems, mental illness, loneliness, and physiological or cognitive dysfunction as well as older adults, who are also more susceptible to poor access to healthcare compared to their more privileged counterparts [18][19][20][21][22]. For example, in Italy during the COVID-19 pandemic, it was found that care delays, reduction in emergency department access, and hospitalisations were more common among older adults with higher number of chronic diseases [22]. In addition, care delays and reduction in emergency department access was more common among older adults with anxiety and depressive symptoms [22].…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the burden and population impact of the COVID-19 pandemic is challenging [ 3 ]. Direct measures of COVID-19 morbidity and mortality are affected by varying testing rates, capabilities and strategies, heterogeneous COVID-19 death definitions and surveillance systems [ 4 , 5 , 6 ]. Overall excess mortality is considered a key measure to understand, compare and monitor the impact of the COVID-19 pandemic over time, both from an epidemiological and public health perspective [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%